Efektivitas Media Murattal Al-Quran Indonesia dalam Pembelajaran Tahfidz di Sekolah Dasar Islam Terpadu Muhammadiyah Bireuen - Hanifah, Nini; Dayusman, Edo Elvizar (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to analyze the effectiveness of Murattal Al-Quran Indonesia media in tahfidz learning at the Integrated Islamic Elementary School (SDIT) Muhammadiyah Bireuen. The research method used is qualitative with a phenomenological approach, which allows researchers to explore the direct experiences of teachers, students, and principals. The research was conducted at SDIT Muhammadiyah Bireuen, which has a superior program of tahfidz Al-Qur'an by using Murattal media as a learning tool. Data were collected through participatory observation, semi-structured interviews, and documentation. The results show that Murattal media is effective in supporting tahfidz learning, as evidenced by the increase in students' memorization achievements, both in quantity and quality, especially in the aspects of tajweed and fluency. This media attracts students' attention and facilitates the memorization process through distinctive rhythms and voice clarity. The constraints faced, such as disruption of student concentration and teacher time constraints, require further attention to improve learning effectiveness. Recommendations from this study include providing training for tahfidz teachers, optimizing time management, and developing features on the Murattal application. Further research is also recommended to explore other digital innovations in tahfidz learning and their impact on students. The findings are expected to make a positive contribution to the development of Qur'an learning methods in Islamic schools.